FPGA Implementation of VLC Communication Technology - Haochang Guo; Ka Lok Man; Qilei Ren; Qian Huang; Hahanov, Vladimir; Litvinova, Eugenia; Chumachenko, Svetlana (IEEE WAINA 2017 : proceedings : 31st IEEE International Conference on Advanced Information Networking and Applications Workshops : 27-29 March 2017, Tamkang University, Taipei, Taiwan, 2017)
Currently, Visible Light Communication (VLC) technology remains a lagging research in the field of UltraWide Band (UWB), due to the inefficiency of data capture and synchronization period. Accordingly, this paper proposes a fundamental designand implementation of data communication of VLC on the MAC layer based on FPGA. This paper includes basic research context, design and implementation of UWB MAC layer, along with the simulation and verification results of this system.